Chiral Colorimetric Detection Of Amino Acids Based On L-Cysteine-Capped Silver Nanoparticles - BENAIDJA Ibtissam; MAACHE Fatna; BOUSSOUAR Imene (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : GÉNIE DES PROCÉDÉS, 2024)
Nanoparticles are generally defined as entities measuring from 1 to 50 nm. Silver particles at the nanoscale exhibit unique properties that make them useful and play an essential role in all scientific and technological fields such as biology, medicine, and optoelectronics. In this study, we created a simple and sensitive colorimetric sensor to detect L-lysine. Silver nanoparticles were decorated with the amino acid L-cysteine. The addition of L-lysine led to the formation of large aggregates of silver nanoparticles, causing changes in color and UV-Visible absorption. This probe demonstrates increased sensitivity and selectivity compared to other optical methods mentioned.
Materials Process Engineering